2016
DOI: 10.1177/0047287516639161
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Destination Marketing

Abstract: Conversion studies are a standard technique by which marketers evaluate advertisement effectiveness. A review of the tourism literature finds that advertising conversion studies use a number of metrics that have evolved to include most aspects of visitor decisions; however, this literature also indicates that there are few comparative studies focusing on the variability of response. The overall goal of this study is to identify and compare estimates of impact on visitor expenditures using four different approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 98 publications
(63 reference statements)
0
1
0
1
Order By: Relevance
“…Kegiatan pemasaran digital biasanya dilakukan melalui website, media sosial, iklan online, email pemasaran langsung, forum diskusi, maupun aplikasi seluler lainnya (Putu Aban Wibawa et al, 2022). Dalam penelitian di bidang pariwisata, efek pemasaran melalui iklan secara visual telah disepakati dapat meningkatkan tanggapan konsumen secara luas (Choe et al, 2016).…”
Section: Tinjauan Pustakaunclassified
“…Kegiatan pemasaran digital biasanya dilakukan melalui website, media sosial, iklan online, email pemasaran langsung, forum diskusi, maupun aplikasi seluler lainnya (Putu Aban Wibawa et al, 2022). Dalam penelitian di bidang pariwisata, efek pemasaran melalui iklan secara visual telah disepakati dapat meningkatkan tanggapan konsumen secara luas (Choe et al, 2016).…”
Section: Tinjauan Pustakaunclassified
“…Few studies, if any, have explored destination quality in its various dimensions and very few have suggested measurement instruments in this context. Indeed, previous research over the past 40 years has revealed that tourism marketing encourages tourists to increase their length of stay, adjust their activity preferences, and even raise expenditure rates (Choe, Stienmetz, and Fesenmaier, 2017), but stakeholders and DMOs' awareness of its importance fail to be explored and documented.…”
Section: Theoretical Implicationsmentioning
confidence: 99%